Program Aplikasi Penerimaan dan Pengeluaran Kas Berbasis Web pada PT Air Minum Tabalong Bersinar (Perseroda) - Nadia Puteri Utami; Fitria Fitria; Khafifah Widya Maharani (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
PT Air Minum Tabalong Bersinar (Perseroda) is a regional-owned business entity engaged in the field of drinking water services for all people in the Tabalong Regency area. A company really needs to carry out internal control over cash receipt and disbursement procedures, because it is related to the continuity of the company's operations. Every day, PT Air Minum Tabalong Bersinar (Perseroda) always supervises cash receipts sourced from water bill income, new connection installations, reconnections, and inspection income. The large amount of cash received every day makes transactions increasingly dense, there is no application to process cash filling and disbursement data, so the calculations are inaccurate, and it is difficult to present cash receipt and disbursement reports briefly. In addition, the problems that occur in cash management, PT Air Minum Tabalong Bersinar (Perseroda) still does the manual method, namely by entering cash receipts and disbursements in Microsoft Excel, and recapitulating data every day by entering it into the table provided. This is less effective and efficient, because it does not shorten the processing time at all and can be risky for data that has not been entered due to unsystematic presentation. Therefore, an application is needed that can handle the current problems, namely the cash receipt and disbursement application to help the process of presenting reports briefly and make it easier for employees to enter data, search for data, and computerized income.